Geographic and taxonomic patterns of extinction risk in Australian squamates. (October 2019) - Tingley, Reid; Macdonald, Stewart L.; Mitchell, Nicola J.; Woinarski, John C.Z.; Meiri, Shai; Bowles, Phil; Cox, Neil A.; Shea, Glenn M.; Böhm, Monika; Chanson, Janice; Tognelli, Marcelo F.; Harris, Jaclyn; et al.
Abstract: Australia is a global hotspot of reptile diversity, hosting 10% of the world's squamate (snake and lizard) species. Yet the conservation status of the Australian squamate fauna has not been assessed for >25 years; a period during which the described fauna has risen by 40%. Here we provide the first comprehensive conservation assessment of Australian terrestrial squamates using IUCN Red List Categories and Criteria. Most (86.4%; n = 819/948) Australian squamates were categorised as Least Concern, 4.5% were Data Deficient, and 7.1% (range 6.8%–11.3%, depending on the treatment of Data Deficient species) were threatened (3.0% Vulnerable, 2.7% Endangered, 1.1% Critically Endangered). This level of threat is low relative to the global average ( 18%). One species ( Emoia nativitatis ) was assessed as Extinct, and two species ( Lepidodactylus listeri and Cryptoblepharus egeriae ) are considered Extinct in the Wild: all three were endemic to Christmas Island. Most (75.1%) threat assessments were based on geographic range attributes, due to limited data on population trends or relevant proxies. Agriculture, fire, and invasive species were the threats that affected the most species, and there was substantial geographic variation in the number of species affected by each threat. Threatened species richness peaked on islands, in the Southern Alps, and across northern Australia. Data deficiency was greatest in northern Australia and in coastal Queensland. Approximately one-in-five threatened species were not represented in a single protected area. Our analyses shed light on the species, regions, and threats in most urgent need of conservation intervention.